The Effect Of Social Media Marketing On Tik Tok Applications On Purchase Decisions At Esana Store - Nasrullah; Sulaiman; Wahyuddin Yahya; Nurinaya (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study aims to determine the effect of Social Media Marketing of Tik Tok Application toward purchase decisions at the Esana Store in Makassar City. Sample uses direct interview with the parties related with the problemjs that being discussed and provides questionnaire the 165 respondents according to the counducted research. The data were analyzed using quantitative methods which is using five formulas as validity test, linear regression, t test and the coefficient of determination by SPSS 25 softwere for windows. The results shows that Social Media Marketing of Tik Tok Application toward Purchase Decisions has positive ang significant effect on Purchase Decisions at the Esana Store in Makassar City.